Ability of fiber bacteria isolated from buffalo rumen in digesting various sources of forage - Iwan Prihantoro; T Toharmat; D Evvyernie; Suryani .; L Abdullah (Jurnal Ilmu Ternak dan Veteriner, 2012)
Local buffalo rumen fluid is a source of fiber digesting bacteria. Such bacteria presumably are well adapted to feed stuffs derived from agricultural byproducts with low quality. The purposes of this study were: (1) to isolate the fiber-digesting bacteria from buffalo rumen fluid, (2) to determine the fiber digesting characteristics and adaptability of such bacteria, and (3) to characterize the bacterial diversity.  Rumen fluids for the experiment were collected from buffaloes slaughtered at the Faculty of Animal Science, Bogor Agricultural University abattoir. Fiber-digesting bacteria were isolated using McDougall buffer supplemented with fibrous feed. A factorial experiment was conducted to study characteristics and adaptability of the bacteria using two factors: the type of bacteria and type of feed source of the fiber. Diversity among the bacteria was analyzed using the NTSys2.10 program.Results showed that nine bacterial isolates had a high adaptability to fiber feed based on CMCase. The highest CMCase activity bacteria for Pennisetum purpureum were A9 (11.36±1.70 unit/ml/h), A3 (11.22±0.60 unit/ml/h) and A42 (10.62±1.96 unit/ml/h). CMCase activity of fiber digesting bacteria from buffalo rumen fluid was not correlated with the number of bacteria in the culture. Based on genetic similarity, nine isolates were grouped into five types having similarity≥46%. Key Words: Buffalo Rumen Fluid, Fiber-Digesting Bacteria, Low Quality Forage